Cold denaturation of staphylococcal nuclease. - Griko, Y V (1988)
Denaturation of staphylococcal nuclease was studied in a temperature range from -7 to 70 degrees C by scanning microcalorimetry and spectropolarimetry. It was found that the native protein is maximally stable at about 20 degrees C and is denatured upon heating and cooling from this temperature. The heat and cold denaturation processes are approximated rather well by a two-state transition showing that the molecule is composed of a single cooperative system. The main difference between these two processes is in the sign of the enthalpy and entropy of denaturation: whereas the heat denaturation proceeds with increases in the enthalpy and entropy, the cold denaturation proceeds with decreases in both quantities. The inversion of the enthalpy sign occurs at about 15 degrees C in an acetate buffer, but this temperature can be raised by addition of urea to the solvent.